Robust topology optimization for continuum structures with random loads. Issue 2 (16th April 2018) - Liu, Jie; Wen, Guilin; Qing, Qixiang; Li, Fangyi; Xie, Yi Min
Abstract : Purpose: This paper aims to tackle the challenge topic of continuum structural layout in the presence of random loads and to develop an efficient robust method. Design/methodology/approach: An innovative robust topology optimization approach for continuum structures with random applied loads is reported. Simultaneous minimization of the expectation and the variance of the structural compliance is performed. Uncertain load vectors are dealt with by using additional uncertain pseudo random load vectors. The sensitivity information of the robust objective function is obtained approximately by using the Taylor expansion technique. The design problem is solved using bi-directional evolutionary structural optimization method with the derived sensitivity numbers. Findings: The numerical examples show the significant topological changes of the robust solutions compared with the equivalent deterministic solutions. Originality/value: A simple yet efficient robust topology optimization approach for continuum structures with random applied loads is developed. The computational time scales linearly with the number of applied loads with uncertainty, which is very efficient when compared with Monte Carlo-based optimization method.